Sustainability of SMEs during COVID-19 Pandemic - James Paul Menina (Research Synergy Foundation, 2023)
Small and Medium Enterprises (SMEs) are vital to the Philippine economy, as the COVID-19 pandemic became more widespread, business activity was negatively impacted, strict quarantine measures were implemented, business operating hours were shortened, and the demand for labor from rural and remote areas decreased. With these new solutions, new measures and protocols are adopted and enforced to protect the safety of employees and consumers. The objective of this study is to determine how the COVID-19 pandemic affected the business sustainability of SMEs. The variables used to assess the impact on businesses are supply chain, business relations, resurging, cash flow, and work remotely. This study focuses solely on registered SMEs that existed before the pandemic and were still operational when the study was conducted. Survey questionnaires were used to gather data from business owners. Responses from the participants were presented in tabular form, along with brief explanations of the results. Statistical evaluation of the hypothesis was conducted using a one-way ANOVA and a two-sample T-test. The results showed the assessment of SME owners regarding the impact of the five variables on the sustainability of their businesses. Importantly, the study highlighted additional measures that can be used to better analyze and evaluate which areas of businesses are impacted by the COVID-19 pandemic and how to keep those businesses afloat.